How do I solve this function?
(x-3)(x-4)
(x-5)(x-6)² =0
Simple Polynomial Multiplication
first three examples are what you want to study
basically its called the FOIL method, I forgot what it means, but I know how to do it and that site shows it better than I could, for the 2nd question you want to take the
(x-6)² = (x-6)(x-6)
Then take that answer and multiply by (x-5)
Follow the sites first 3 examples and you'll be golden
*edit*
Ok I remembered, FOIL is FIRST OUTER INNER LAST, Basically you would take
(x-5)(x-6)=
First = (x)(x)
outer= (x)(-6)
Inner=(x)(-5)
LAST=(-5)(-6)
combined it gives you this : (x)(x) + (x)(-6) + (x)(-5) + (-5)(-6)
Which gives you the answer to that problem but not yours, you gotta do your problem yourself No fun in me doing it for you! wait, that kind of is your problem, blast!